1994
DOI: 10.1677/jme.0.0120351
|View full text |Cite
|
Sign up to set email alerts
|

Human relaxins in normal, benign and neoplastic breast tissue

Abstract: Immunoreactive relaxin is present in human breast cyst fluid and postpartum milk without concurrent detectable serum levels, suggesting that the breast is a site of relaxin synthesis. Monoclonal and polyclonal antibodies to human relaxin H2 have been used to immunolocalize relaxins in normal, benign and neoplastic breast tissues with the avidin-biotin immunostaining technique. In view of the similarities in amino acid sequence between H1 and H2 relaxins, these antibodies to H2 relaxin are likely to detect eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 0 publications
3
76
0
Order By: Relevance
“…These data support our finding that increased H2 relaxin expression is associated with AI growth of CaP. A functional role for H2 relaxin in the progression of other cancers has also been demonstrated (Stemmermann et al, 1994;Tashima et al, 1994). Treatment of a breast cancer cell line, MCF-7, with H2 relaxin increased both cell proliferation and invasiveness (Tashima et al, 1994).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These data support our finding that increased H2 relaxin expression is associated with AI growth of CaP. A functional role for H2 relaxin in the progression of other cancers has also been demonstrated (Stemmermann et al, 1994;Tashima et al, 1994). Treatment of a breast cancer cell line, MCF-7, with H2 relaxin increased both cell proliferation and invasiveness (Tashima et al, 1994).…”
Section: Discussionsupporting
confidence: 89%
“…A functional role for H2 relaxin in the progression of other cancers has also been demonstrated (Stemmermann et al, 1994;Tashima et al, 1994). Treatment of a breast cancer cell line, MCF-7, with H2 relaxin increased both cell proliferation and invasiveness (Tashima et al, 1994). Other studies have demonstrated that H2 relaxin plays a role in processes associated with cancer progression.…”
Section: Discussionmentioning
confidence: 95%
“…Studies in other species indicate that relaxin of maternal origin could be an important source of the hormone in the neonate by way of ingestion of colostrum and milk. Relaxin is detectable in human (Eddie et al 1989) and canine (Goldsmith et al 1994) colostrum and milk, and mammary tissue has been suggested as a local source of relaxin (Tashima et al 1994). Like other peptide growth factors in milk, relaxin may contribute to early neonatal development (Burrin et al 1997, Anderson et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…The systemic relaxin acting in this way is the H2 form and the only relaxin produced by the human corpus luteum (Hudson et al 1984). It has been shown, however, that relaxins are also autocrine/paracrine hormones in a number of other tissues such as prostate (Hansell et al 1991), placenta (Sakbun et al 1990), endometrium, decidua (Bryant-Greenwood et al 1993) and mammary gland (Tashima et al 1994). When relaxins are produced and act locally in this manner, both relaxin genes are expressed (Bryant-Greenwood & Schwabe 1994).…”
Section: Introductionmentioning
confidence: 99%